Detecting behavioural change in conversation: procedures and preliminary data. Issue 7 (3rd July 2021) - Azios, Jamie H.; Archer, Brent; Lee, Jaime B.
ABSTRACT: Background: Improvement in daily life activities such as conversation has been prioritized by people with aphasia, which has led to an increased interest in developing and evaluating therapies that target conversation abilities. However, many questions remain about reliable and valid procedures for examining outcomes related to conversation. In this paper, we detail a procedure for quantifying conversational behaviours to improve the protocol described in previous interaction-focused studies and report preliminary data on the effects of a conversation-based intervention using the refined protocol. Methods & Procedures: To address the first aim, the authors reviewed procedures developed for previous interaction-focused interventions and included additional practices in the procedure to increase experimental control, ensure similarity across samples, and capture reliability data. To address the second aim, a multiple baseline single case experimental design was employed to examine potential treatment effects associated with a conversation-based intervention across two participants with aphasia. Outcomes & Results: Krippendorff's alpha statistics revealed inter-rater reliability scores ranging from 0.81 to 0.98 for identifying conversation-based outcomes. Visual inspection and statistical analysis of intervention data revealed improvement in frequency of conversation strategy usage over baseline levels and medium to large treatment effects for two of the three strategies targeted in both participants. Conclusions: Results of this study, coupled with findings from previous studies of conversation intervention, add to the growing body of literature which highlights the possible efficacy of interaction-focused intervention and the therapeutic value of natural contexts such as conversation. Developing effective, conversation-based therapies will help to bring treatment practices into closer alignment with client values which tend to emphasize conversational abilities as therapeutic targets.